Taming private Leviathans: regulation versus taxation - Arezki, R; Islam, A; Rota-Graziosi, G (University of Oxford, 2021)
This paper explores the interplay between top wealth and policies namely regulation and taxation exploiting variation in exposure to international commodity prices. Using a global panel dataset of billionaire’s net worth, results point to a positive relationship between commodity prices and the concentration of wealth at the top. Regulation especially pertaining to competition is found to limit the effects of commodity price shocks on top wealth concentration while taxation has little effect. Moreover, commodity price shocks crowd out non-resource tax revenue hence limiting the scope for income transfers and redistribution. Results are consistent with the primacy of ex ante interventions over ex post ones to address top wealth inequality.